"A Space Where People Get It": A Methodological Reflection of Arts-Informed Community-Based Participatory Research With Nonbinary Youth. Issue 1 (18th July 2019) - Furman, Ellis; Singh, Amandeep K.; Wilson, Ciann; D'Alessandro, Fil; Miller, Zev
This article is a methodological reflection of Bye Bye Binary, a community-based participatory research project (CBPR) that explored nonbinary youths' experiences of identity development, engagement in activism, discrimination, and mental health in Ontario, Canada. The arts-informed method of body mapping was employed in a workshop format to garner the experiences of 10 nonbinary youth (aged 16–25), in conjunction with additional qualitative methods (i.e., individual interviews and reflective notes). Findings suggest that the body-mapping workshop fostered a safe environment that promoted idea generation, affirmation, self-exploration, and connections through a shared identity, thus creating "a space where people get it." Methodological challenges that arose throughout the process are discussed, including engagement in art as "awkward, " barriers of limited time and funding, participant recruitment, and collaboration and integration. Lastly, the authors reflect on their learnings engaging in CBPR and provide insights into how researchers can move forward and apply these methods and processes into their own work engaging in arts-informed research or with nonbinary individuals.